2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24080
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Social Processes of Ethics in Student Engineering Design Teams

Abstract: Megan is a fourth year doctoral candidate in the Brian Lamb School of Communication at Purdue University pursuing a Ph.D. in Organizational Communication with a minor in mixed methods. Her research focuses on engineering education, design, organizational identity, identification and socialization, team communication, innovation, and technology. She is currently working on an NSF grant examining ethical reasoning and decision-making in engineering project teams, and examining the relationship between teams and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…[16][17][18][19] Typically these efforts concentrate on the nature of the interactions and the interpersonal/intergroup dynamics. 14,[20][21][22][23] Examination at this micro-level is vital to understanding how relationships are formed, but tends to ignore the larger social structures of an environment. Examining the interaction patterns (i.e., the social structure) of students creates an understanding of how individuals are included in developing communities, "even a single time-slice of the social network of a class, which shows the social ties between the students, can reveal much about a student's position in the network."…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Typically these efforts concentrate on the nature of the interactions and the interpersonal/intergroup dynamics. 14,[20][21][22][23] Examination at this micro-level is vital to understanding how relationships are formed, but tends to ignore the larger social structures of an environment. Examining the interaction patterns (i.e., the social structure) of students creates an understanding of how individuals are included in developing communities, "even a single time-slice of the social network of a class, which shows the social ties between the students, can reveal much about a student's position in the network."…”
Section: Introductionmentioning
confidence: 99%
“…A feature of business communication is that, mostly, it is determined by national cultural traditions and professional ethical principles [5]. The prospect of developing business international interaction lies on the path from the clash of cultures to uniting and forming on their universal moral basis the provisions of a single international business culture [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our work to date indicates that students' attitudes about diversity are difficult to shift towards greater inclusivity within a semester-long experience, even with explicit instruction and instructor support [8]. Furthermore, we have shown that working with diverse peers is an integral part of developing openness towards diversity, reaffirming that the experience of working with diverse peers is a vital step in the process of creating inclusive engineering environments [9]- [13]. However, we have shown that working in diverse engineering teams alone does not ensure an inclusive environment.…”
Section: Synopsis Of Prior Workmentioning
confidence: 51%